Deconstruction of semi-Orientalism and Balkanism in the Autobiographical Prose of Enzo Bettiza and Grytzko Mascioni - Dalmatin, Katarina (Anafora, 2025)
The paper analyses the ways of deconstructing some dominant elements of semi-Orientalist and Balkanist discourse (as defined by Nino Raspudić and Maria Todorova) in the autobiographical prose of Enzo Bettiza and Grytzko Mascioni of the late 20th century. In the context of Bettiza’s deconstruction of Balkan myths about the causes and nature of the war in Croatia and Bosnia and Herzegovina in the 1990s in Esilio (Eng. The Exile), the paper focuses on his analysis of the role of the negative perception of elements of the Ottoman heritage in the creation of the ideological framework of the Greater Serbian ideology, as well as on the different functions of depicting Dalmatian hill people (Vlaji) in Esilio compared to those that motivated the depictions of Morlachs in the Italian semi-Orientalist tradition of the late 20th century. In the novel Puck by Grytzko Mascioni, the distancing from the Adriatic semi-Orientalist discourse is manifested in the refusal to attribute the cultural achievements of Dalmatia exclusively to Venetian and Italian influence, and in the privileged position of Dubrovnik in the representation of Croatian and Dalmatian identity. The detachment from semi-Orientalism in Puck takes the form of a strong intertextual dialogue with the birthplace of this discourse – Alberto Fortis’s Travels into Dalmatia.